Elevated international normalized ratio (INR) and new diagnosis of hepatitis C associated with severe intrahepatic cholestasis of pregnancy (ICP): A case report - Courtney Birchall; Danielle Prentice; Jaimey Pauli (Elsevier, 2020)
Background: Severe intrahepatic cholestasis of pregnancy (ICP), defined as a serum bile acid (SBA) level > 100 μmol/l, remains poorly understood in its mechanism and implications. Case: A patient with a missed diagnosis of mild ICP went on to develop clinical jaundice and liver function abnormalities in the setting of newly diagnosed hepatitis C and severe ICP on repeat SBA testing. Conclusion: This case highlights and adds to the growing body of evidence supporting the need for universal screening for hepatitis C in ICP patients and the potential role for repeat SBA testing, which would be a notable change from the traditional care of these individuals. Keywords: Cholestasis, Hepatitis C, Bile acids, Pregnancy